Answer:
-56
Step-by-step explanation:
f(x) = 7x + 7
x = -9
We meed to plug in x = -9 into the first equation:
f(-9) = 7(-9) + 7
We can open up the parentheses:
f(-9) = -63 + 7
And then simplify:
f(-9) = -56
8/10 = 4/5 divide each by 2
Answer:
the cyclists rode at 35 mph
Step-by-step explanation:
Assuming that the cyclists stopped, and accelerated instantaneously at the same speed than before but in opposite direction , then
distance= speed*time
since the cyclists and the train reaches the end of the tunnel at the same time and denoting L as the length of the tunnel :
time = distance covered by cyclists / speed of cyclists = distance covered by train / speed of the train
thus denoting v as the speed of the cyclists :
7/8*L / v = L / 40 mph
v = 7/8 * 40 mph = 35 mph
v= 35 mph
thus the cyclists rode at 35 mph